Alexander Campbell: adventurer in freedom : a literary biography / Volume 1 - Wrather, Eva Jean; Cummins, D. Duane (TCU Press, 2005)
bk. 1. The twig is bent (1788-1809) -- bk. 2. The way is prepared (1809-1822).